Spiral Computed Tomography Based Maxillary Sinus Imaging in Relation to Tooth Loss, Implant Placement and Potential Grafting Procedure - Reinhilde Jacobs; Dong Xue; Yuqian Hu; Johan van Cleynenbreugel; Maryam Shahbazian (eJournal of Oral Maxillofacial Research)
Objectives: The purpose of the present study was to explore the maxillary sinus anatomy, its variations and volume in patients with a need for maxillary implant placement.Materials and Methods: Maxillary sinus data of 101 consecutive patients who underwent spiral computed tomography (CT) scans for preoperative implant planning in the maxilla at the Department of Periodontology, University Hospital, Catholic University of Leuven, Leuven, Belgium were retrospectively evaluated. The alveolar bone height was measured on serial cross-sectional images between alveolar crest and sinus floor, parallel to the tooth axis. In order to describe the size of the maxillary sinus anteroposterior (AP) and mediolateral (ML) diameters of the sinus were measured.Results: The results indicated that the alveolar bone height was significantly higher in the premolar regions in comparison to the molar region (n = 46, P < 0.01). The age showed negative relation to bone dimension (r = - 0.32, P = 0.04).Anterior and posterior border of the maxillary sinuses were mostly located in the first premolar (49%) and second molar (84%) regions, respectively. Maxillary sinus septa were indentified in 47% of the maxillary antra. Almost 2/3 (66%) of the patients showed major (> 4 mm) mucosal thickening mostly at the level of the sinus floor. The present sample did not allow revealing any significant difference (P > 0.05) in maxillary sinus dimensions for partially dentate and edentulous subjects.Conclusions: Cross-sectional imaging can be used in order to obtain more accurate information on the morphology, variation, and the amount of maxillary bone adjacent to the maxillary sinus.